Representación de los colectivos GLBTI en el periodismo de información de diario La Prensa, periodo 2022. - Pérez Guaman, Guillermo Wanderley (2024)
ABSTRACT: The attention of the media has been at the service of the needs of society. Nonetheless, concerns pertaining to the GLBTIQ+ population continue to be low on the public and media agendas even today. GLBTI individuals have traditionally faced violence, abuse, rejection, and persecution in Ecuador, especially under the León Febres Cordero administration. But despite this, the media fails to give the collective the coverage they deserve, and their issues are viewed as secondary. Thus, the current study aims to examine the existence of the GLBTI community by breaking down the kinds of content that are made available to the general public and examining how the Riobamba daily media, La Prensa, handles information. To achieve the research objectives, a qualitative-quantitative methodology was used, as it allowed specifically collecting the number of notes published by the newspaper, and at the same time, organizing them into categories for analysis. In addition, to hear the opinions of both sides, interviews with the editor of the newspaper La Prensa and a member of the LGBTIQ+ community were conducted. Although the medium is satisfied with the vulnerable areas and the collective feels represented in the public realm, in our opinion, the outcomes do not demonstrate the visibility of the collective. Minority groups still require media attention for their visibility, inclusion and diversity. Even today they are stigmatized for their preferences, and therefore, these groups need the help of newspapers to avoid the stereotypes, prejudices and discrimination that exists towards this community.